Non-Invasive Diagnosis of Polypoidal Choroidal Vasculopathy as a Variant of the Course of Age-Related Macular Degeneration - I. E. Panova; T. B. Shaimov; V. A. Shaimova (Oftalʹmologiâ)
Purpose: to study noninvasive diagnostic options for polypoidal choroidal vasculopathy (PCV) — a subtype of neovascular agerelated macular degeneration — by monitoring clinical progression, defining optical coherence tomography (OCT) findings specific for PCV and evaluating diagnostic utility of OCT angiography.Patients and methods. The study included 254 patients (292 eyes) with neovascular age-related macular degeneration. All patients underwent complex eye examination: visual acuity test, slit lamp biomicroscopy, ophthalmoscopy with 60 and 78D fundus lenses, fundoscopy with color filters, spectral-domain OCT, OCT angiography and biometry. Fluorescein angiography was performed in 66 cases. Indocyanine green angiography was employed in 16 patients with PCV. All statistical analyses were performed with IBM SPSS Statistics 19 software package.Results. In 14 of 16 patients (87.5%) indocyanine green angiography revealed round hyperfluorescent lesions which corresponded to ophthalmoscopy findings — subretinal reddish orange nodules localized primarily in the parafovea. In 11 cases (68.8%) the nodules were associated with hemorrhage and in 14 cases (87.5%) — with hard yellowish exudates. Comparative analysis of retinal anatomy allowed for defining typical OCT signs of PCV that distinguish the clinical entity from type 1 and 2 choroidal neovascular membranes: neurosensory retinal detachment in the parafovea (80.0%, p < 0.001) and hard exudates (71.9%, p < 0.001). OCT findings characteristic of PCV are dome-shaped pigment epithelium detachment (100%), bubble sign (94.74%), notch sign (68.4%) and double layer sign (92.9%).Conclusion. Noninvasive diagnosis of polypoidal choroidal vasculopathy should encompass clinical signs, fundoscopy findings, OCT-based morphometry and OCT angiography criteria. OCT angiography has high diagnostic value and enables detection of branching vascular network and polypoidal formations.